DX-9065a inhibition of factor Xa and the prothrombinase complex: mechanism of inhibition and comparison with therapeutic heparins - Rezaie, Alireza R. (Thrombosis and Haemostasis, 2003)
Factor Xa (fXa) is the key enzyme of the prothrombinase complex that generates thrombin hence it is a good target for antithrombotic therapy. Here, the anti-fXa and anti-prothrombinase activities of DX-9065a which is an active-site directed inhibitor of fXa, and therapeutic heparins which are dependent on antithrombin (AT) for their anticoagulant function, were studied in amidolytic and proteolytic activity assays. It was found that DX-9065a is a competitive inhibitor of the Spectrozyme FXa (SpFXa) cleavage by both fXa and prothrom-binase with similar Ki values of ~10-20 nM. However, DX-9065a acted as a non-competitive inhibitor of prothrombin activation by prothrombinase with a Ki of ~26 nM. On the other hand, therapeutic heparins were effective catalysts of both fXa and prothrombinase inhibition by AT in the presence of SpFXa, but were ineffective in the presence of prothrombin. Further studies revealed that Tyr99, a residue in the extended S2-S4 binding pocket of fXa, plays a key role in determination of specificity of the DX-9065a interaction.
Keywords: Factor Xa; prothrombinase; DX-9065a; antithrombin; heparin